(untitled) (Journal of Medicine, 2017)
Marfan Syndrome is an autosomal dominant disorder caused by mutation in the extracellular matrix protein fibrilin-1 gene located on chromosome 15. It has variable range of expression.We describe a case of a 12 year aged girl with positive family history including lean and thin body stature, skin striae, joint hyper mobility, high arched palate, mal occlusion of teeth, pectus excavatum, winging of scapula, scoliosis of back bone, total arm span more than total body height (1.11:1), lower segment greater than upper segment (1.40:1), severe form of mitral valve prolapse and aortic root dilatation. There are a lot of features of Marfan Syndrome in our single patient which is rare in earlier available case reports. J MEDICINE Jan 2018; 19 (1) : 58-62